Retrospective Analysis of Cervical Cancer Staging in two Cohorts and its Application in 2018 Revised FIGO Staging for Cancer Cervix (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Introduction: cervical cancer is the second most common cancer of women in Bangladesh. Information about the extent of any cancer is critical for treatment planning .For the management of cervical cancer clinical staging is the first and foremost task and disease stage is the single most important prognostic factor.Objective: To know the distribution of clinical stages of cervical cancer, to validate the revised 2018 FIGO staging system for cervical cancer with a particular focus on stage 1B and to know the differences in distribution of stages among two cohort groups.Methods: Retrospective analysis was conducted among two cohorts of cervical cancer patients. First group of cervical cancer patients underwent Examination Under Anesthesia (EUA) for clinical staging during December 2011 to July 2017 and second cohort was the same type of patients undergoing same procedure by different group of observer from August 2017 to June 2019. Chi square test was done to know the difference in stages between two groups. P value